2004
DOI: 10.1097/01.tp.0000137322.65953.0a
|View full text |Cite
|
Sign up to set email alerts
|

Early Cyclosporine A Withdrawal in Kidney-Transplant Recipients Receiving Sirolimus Prevents Progression of Chronic Pathologic Allograft Lesions

Abstract: Early cyclosporine withdrawal associated with sirolimus administration is followed by an improvement in renal function, a reduction in the progression of chronic pathologic allograft lesions, and a lower incidence of new cases and severity of CAN during the first year after transplantation. This benefit may result in better long-term graft outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 25 publications
2
44
1
1
Order By: Relevance
“…Although the comparator arm uses combination CSA and sirolimus, which would now be expected to yield poor results, this cannot obviate significant improvements within the other arm. Similar histopathologic results have been seen in other smaller trials (104,105), supporting the view that the TORi lead to better long-term graft histology and reduced chronic allograft dysfunction.…”
Section: Therapeutic Strategies In Chronic Renal Dysfunctionsupporting
confidence: 77%
“…Although the comparator arm uses combination CSA and sirolimus, which would now be expected to yield poor results, this cannot obviate significant improvements within the other arm. Similar histopathologic results have been seen in other smaller trials (104,105), supporting the view that the TORi lead to better long-term graft histology and reduced chronic allograft dysfunction.…”
Section: Therapeutic Strategies In Chronic Renal Dysfunctionsupporting
confidence: 77%
“…However, the prevalence of mild hyalinosis increased from (20) or re-operations (3). 3 Chronicity score equals the sum of Banff chronic scores (ah + eg + ci + ct + cv).…”
Section: Discussionmentioning
confidence: 99%
“…However, one of these studies compared tacrolimus and cyclosporine-treated patients, in both of whom the prevalence of CAN was approximately 70% at 2 yr (24). Finally, two recent studies reported the prevalence of CAN in protocol biopsies in patients who were on sirolimus (37,38). In one study (37), approximately 32% of patients who switched to sirolimus at 3 mo had new-onset CAN at 1 yr, as compared with 65% of those who were maintained on cyclosporine.…”
Section: Interstitial Fibrosis and Tubular Atrophy: Prevalence Risk mentioning
confidence: 99%
“…Finally, two recent studies reported the prevalence of CAN in protocol biopsies in patients who were on sirolimus (37,38). In one study (37), approximately 32% of patients who switched to sirolimus at 3 mo had new-onset CAN at 1 yr, as compared with 65% of those who were maintained on cyclosporine. In the other study (38), patients who were randomly assigned to sirolimus had a 34% prevalence of CAN at 2 yr as compared with almost 80% for those who were on cyclosporine.…”
Section: Interstitial Fibrosis and Tubular Atrophy: Prevalence Risk mentioning
confidence: 99%